Editorial: Flexible Syk: turning on and off the inflammasome as needed. Issue 5 (1st May 2015) - Fitzpatrick, Elizabeth
Abstract : Discussion on Syk tyrosine kinase functioning as a positive and negative regulator of NLRP3 inflammasome activation.